Flame-Spread Behavior Of Biodiesel (B20) In A Microgravity Environment - Saputro, Herman; Fitriana, Laila; Abdul Munir, Fudhail; Mikami, Masato (The Japan Society of Mechanical Engineers, 2020)
Indonesia has implemented a policy of using diesel fuel containing 20 percent biofuel (commonly known as B20 biodiesel), as stated in Energy and Mineral Resources Ministerial Decree No. 23/2013. This study investigated the flame-spread characteristics of biodiesel (B20) in a microgravity environment through drop tower facilities. This is due to the difficulty in creating droplet sizes similar to the real liquid sprays in the combustion chamber of diesel engines. The experiment used biodiesel (B20) droplets with a diameter 1 mm. The results show that the biodiesel (B20) droplets have characteristics of a flame–spread limit distance SBC/dC0limit = 7. This paper discusses the characteristics of biodiesel (B20) droplets in detail.